Choline ionic liquid, synthesis method and application thereof as electrolyte additive for magnesium-air battery
By adding choline-based ionic liquid to the electrolyte of magnesium air battery, the problems of low discharge voltage and low specific energy of magnesium air battery are solved, and the discharge performance of magnesium air battery is significantly improved.
Patent Information
- Application Number
- CN202211577325.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-09
AI Technical Summary
During the discharge process, magnesium air batteries have problems such as low anode discharge voltage and low specific energy, which is mainly due to the self-corrosion of the magnesium negative electrode and the coverage of the discharge product, resulting in the reduced contact between the reaction surface and the electrolyte solution.
Choline-type ionic liquid is used as an electrolyte additive to form a bifunctional ionic liquid by combining choline cations with acid anions, which slows down the self-corrosion of the magnesium anode and hinders the generation of insoluble discharge products, thereby increasing the discharge voltage and specific energy of the magnesium air battery.
It significantly improves the discharge voltage and specific energy of magnesium air batteries, improves the discharge performance of magnesium air batteries, and is suitable for different types of magnesium anode materials.
Smart Images

Figure CN116239463B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium-air batteries, and in particular relates to a choline ionic liquid, a synthesis method and an application of the choline ionic liquid as an electrolyte additive for magnesium-air batteries. Background Art
[0002] In recent years, energy crisis and environmental pollution have become increasingly serious. The development of new energy is crucial to the sustainable development of human life and economy.
[0003] Magnesium-air battery is a special type of fuel cell and one of the representatives of the new generation of green batteries. It has the advantages of excellent discharge performance, high safety performance, low cost, light weight, non-toxicity, pollution-free, and high specific energy. It has abundant resources and can be recycled. It is simpler in structure than hydrogen fuel cells and is a new energy source with great development and application prospects. The energy of a general battery is stored in its two electrode materials, while the magnesium-air battery uses the anode, which is a metal electrode, to store energy. The air electrode is used as a tool to convert energy and reduce oxygen in the air to complete the redox process. The theoretical voltage of the magnesium-air battery is 3.1 V, which is much larger than that of lithium-air batteries (2.9 V) and aluminum-air batteries (2.7 V); the theoretical energy density is 6800 WhKg -1 , is a lithium-ion battery (387 Wh Kg -1 ) is 18 times.
[0004] Although magnesium-air batteries have relatively high voltage and energy density, they have problems of low utilization and low voltage during discharge, which limits their widespread application. There are two reasons for these two problems:
[0005] 1) During the discharge process, the magnesium negative electrode suffers from severe self-corrosion, such as microgalvanic corrosion caused by impurities or second phases, “block effect” caused by metal particles falling off the anode surface, and negative difference effect;
[0006] 2) The surface of the magnesium anode is usually covered with discharge products, such as Mg(OH)2 and MgO, which hinder the contact between the reaction surface and the electrolyte, thereby reducing the discharge voltage.
[0007] The most commonly used electrolyte for magnesium-air batteries is salt water. The general practice is to add NaCl to the magnesium-air battery. When it is needed, water is added to induce the reaction. When it is not in use, the water and the magnesium anode material are isolated to stop the discharge. Electrolyte modification is an effective strategy to improve the actual performance of magnesium-air batteries. The most commonly used electrolyte for magnesium-air batteries is 3.5wt.% NaCl. Adding additives to the electrolyte can not only reduce the deposition of Mg(OH)2 on the surface of the magnesium anode, but also inhibit the hydrogen evolution reaction at the anode and slow down the self-corrosion of the anode, thereby achieving the purpose of improving the performance of magnesium-air batteries. The additives used in magnesium-air batteries are different from the corrosion inhibitors used for other magnesium alloy materials. On the one hand, it is necessary to inhibit the self-corrosion reaction of the magnesium alloy anode, but on the other hand, it is conducive to the smooth and continuous redox reaction of the alloy anode, reducing and preventing the adsorption of magnesium hydroxide on the magnesium alloy anode.
[0008] Based on this, the present invention provides a class of choline ionic liquids, a synthesis method and an application thereof as an electrolyte additive for magnesium-air batteries. Summary of the invention
[0009] The present invention aims to overcome the defects of the prior art and provide a class of choline ionic liquids, which can be used as additives for magnesium-air battery electrolytes to increase the discharge voltage and specific energy of magnesium-air batteries, thereby significantly improving the discharge performance of the battery.
[0010] The present invention also provides a simple synthesis method of the choline ionic liquid and application of the choline ionic liquid as an electrolyte additive for magnesium-air batteries.
[0011] To achieve the above object, the present invention adopts the following technical solution:
[0012] Choline ionic liquid, which is composed of any one or more compounds represented by the following molecular structural formula:
[0013] .
[0014] A method for synthesizing the above-mentioned choline ionic liquid specifically comprises the following steps:
[0015] The choline hydroxide is mixed with the acid compound and distilled water, and then stirred at room temperature for reaction for 12-24 hours. After the reaction is completed, the mixture is subjected to rotary evaporation and dried to obtain the product.
[0016] In the above-mentioned synthesis method, the acid compound can be one or more of glycolic acid, salicylic acid and 8-hydroxyquinoline-5-sulfonic acid.
[0017] In the above-mentioned synthesis method, the molar ratio of choline hydroxide to the acid compound is 1: 1. For example, 0.1 mol of choline hydroxide and 0.1 mol of glycolic acid can be added, and 70-100 mL of distilled water can be added accordingly.
[0018] The present invention provides application of the choline ionic liquid as an electrolyte additive for magnesium-air batteries.
[0019] The present invention also provides a magnesium-air battery, which comprises an anode material, an air cathode and an electrolyte containing the choline ionic liquid as an additive.
[0020] In the magnesium-air battery mentioned above, specifically, the electrolyte is 3.5 wt.% NaCl (mass percentage).
[0021] In the above-mentioned magnesium-air battery, the anode material may be one or more of Hp-Mg (high-purity magnesium), AM50, AZ31 and ZK61 alloys. In the magnesium-air battery, the air cathode may be composed of a gas diffusion layer, a current collecting layer and a catalyst layer, and the catalyst layer includes a manganese dioxide catalyst. The air cathode may be directly purchased from a common commercial product, or may be prepared according to conventional techniques in the art.
[0022] The present invention provides the use of the above-mentioned choline ionic liquid as an electrolyte additive for magnesium-air batteries. A magnesium-air battery is assembled with Hp-Mg as an anode, 3.5 wt.% NaCl as an electrolyte and an air cathode. After the choline ionic liquid ([Ch][GA], [Ch][SAL] and [Ch][HQSA]) described in the present invention is added to the electrolyte, the discharge voltage and specific energy of the magnesium-air battery are greatly improved. In addition, the [Ch][SAL] ionic liquid is also applied to magnesium-air batteries assembled with AM50, AZ31 and ZK61 alloys as anode materials, which also show good discharge performance.
[0023] The present invention aims to solve the problem of low anode discharge voltage and low specific energy of magnesium-air batteries. The present invention combines choline cations with glycolic acid, salicylic acid and 8-hydroxyquinoline-5-sulfonic acid anions to form a bifunctional ionic liquid. The anions in the ionic liquid are Mg 2+ An effective complexing agent that can react with OH - Competition Mg 2+, reducing the generation of insoluble discharge products Mg(OH)2 and MgO, which is conducive to direct contact between the magnesium anode and the electrolyte. The choline cation is a quaternary ammonium salt derivative, and the central nitrogen atom is surrounded by three methyl groups and one hydroxyethyl group, which provides hydrophobic and hydrophilic conditions and is usually used as a corrosion inhibitor for metals. Based on this, they are determined to be additives for magnesium-air battery electrolytes to improve the discharge performance of the battery. Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0024] (1) The choline ionic liquid of the present invention has the advantages of low raw material price, low pollution, simple synthesis method, mild reaction conditions, and no need for complicated post-treatment, etc. It can significantly improve the discharge performance of magnesium-air batteries and has good application prospects;
[0025] (2) In the choline ionic liquid of the present invention, the choline cation is a corrosion inhibitor for the anode of the magnesium air battery, which can effectively slow down the self-corrosion of the magnesium anode, and the anion is Mg 2+ It is an effective complexing agent that can hinder the formation of insoluble discharge products;
[0026] (3) The choline ionic liquid of the present invention is used as an electrolyte additive, and the discharge voltage and specific energy of the magnesium-air battery are greatly improved, thereby improving the discharge performance of the magnesium-air battery with Hp-Mg as the anode. In addition, the choline ionic liquid as an additive is also suitable for magnesium-air battery systems with AM50, AZ31 and ZK61 alloys as anodes, and has good universality. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Discharge curves and specific energy diagrams of magnesium-air batteries assembled with Hp-Mg anode in blank and choline-containing ionic liquid electrolytes: (a) 1 mA cm -2 ; (b) 2.5 mA cm -2 ; (c) 5 mA cm -2 ; (d) specific energy diagram;
[0028] Figure 2 Discharge curves and specific energy diagrams of magnesium-air batteries assembled with three types of anodes in 0.1 M [Ch]SAL] electrolyte: (ab) 1 mA cm -2 ; (cd) 2.5 mA cm -2 ; (ef) 5 mA cm -2 . DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described in detail below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto.
[0030] In the following embodiments and application examples, unless otherwise specified, all raw materials used are common commercial products that can be directly purchased in the art. Room temperature refers to 25±5°C.
[0031] Example 1
[0032] The synthesis method of choline glycolate ionic liquid ([Ch][GA]) comprises the following steps:
[0033] Add 25.0 g (0.1 mol) of choline hydroxide (48.5 wt.% in H2O) and 10.86 g (0.1 mol) of glycolic acid (70 wt.% in H2O) to a single-necked flask, then add 80 mL of distilled water to the mixture and stir for 24 h at room temperature and pressure. After the reaction is completed, 60 °C rotary evaporation is performed to obtain a viscous liquid. The product is further dried in a vacuum oven at 60 °C for 24 h. The obtained brown-yellow viscous liquid is the [Ch][GA] ionic liquid; the structural formula is as follows:
[0034] ;
[0035] The graph information is as follows:
[0036] 1 H NMR (300 MHz, D2O): δ 4.01 (t, 2H), 3.89 (s, 2H), 3.46 (t, 2H), 3.15 (s, 9H). 13 CNMR (75 MHz, DMSO- d 6 ): δ 175.43, 67.53, 61.97, 55.50, 53.56.
[0037] Example 2
[0038] A method for synthesizing choline salicylic acid ionic liquid ([Ch][SAL]) comprises the following steps:
[0039] Add 25.0 g (0.1 mol) of choline hydroxide (48.5 wt.% in H2O) and 13.8 g (0.1 mol) of salicylic acid to a single-necked flask, then add 80 mL of distilled water to the mixture, and stir and react for 24 h at room temperature and atmospheric pressure. After the reaction is completed, 60 °C rotary evaporation is performed to obtain a viscous liquid. The product is further dried in a vacuum oven at 60 °C for 24 h. The obtained dark red viscous liquid is the [Ch][SAL] ionic liquid; the structural formula is as follows:
[0040] ;
[0041] The graph information is as follows:
[0042] 1 H NMR (300 MHz, DMSO- d 6): δ 7.74 (d, J = 7.6 Hz, 1H), 7.20 (t, J = 6.7Hz, 1H), 6.73-6.63 (m, 2H), 3.88 (t, 2H), 3.47 (t, 2H), 3.16 (s, 9H). 13 C NMR (75 MHz, DMSO- d 6): δ 171.59, 162.71, 131.52, 129.96, 120.23, 116.11, 115.84, 67.05, 55.14, 53.09.
[0043] Example 3
[0044] A method for synthesizing choline 8-hydroxyquinoline-5-sulfonic acid ionic liquid ([Ch][HQSA]) comprises the following steps:
[0045] Add 25.0 g (0.1 mol) of choline hydroxide (48.5 wt.% in H2O) and 22.5 g (0.1 mol) of 8-hydroxyquinoline-5-sulfonic acid to a single-necked flask, then add 80 mL of distilled water to the mixture, and stir and react for 24 h at room temperature and atmospheric pressure. After the reaction is completed, 60 ° C rotary evaporation is concentrated to obtain a viscous liquid. The product is further dried in a vacuum oven at 60 ° C for 24 h. The obtained brown-yellow viscous liquid is the [Ch][HQSA] ionic liquid; the structural formula is as follows:
[0046] ;
[0047] The graph information is as follows:
[0048] 1 H NMR (300 MHz, DMSO- d 6 ) δ 9.14 (d, 1H), 8.82 (d, J = 5.5 Hz, 1H), 7.87(d, J = 8.0 Hz, 1H), 7.58 (t, 1H), 6.98 (d, J = 8.0 Hz, 1H), 3.81 (t, J = 7.3Hz, 2H), 3.40 (t, 2H), 3.10 (s, 9H). 13C NMR (75 MHz, DMSO- d 6 ) δ 155.23, 147.35, 138.78, 135.78, 133.64, 126.07, 125.33, 121.28, 108.86, 66.92, 55.17, 53.11.
[0049] Application Example 1
[0050] The effect of the choline ionic liquid of the present invention on the discharge performance of an Hp-Mg-based magnesium-air battery in a 3.5 wt.% NaCl electrolyte.
[0051] A magnesium-air battery was assembled using high-purity magnesium (Hp-Mg, the composition of which is: 0.0006 wt.% Al, 0.0021 wt.% Zn, 0.0014wt.% Si, 0.0019 wt.% Fe, 0.0003 wt.% Cu, 0.0003 wt.% Ni, 0.0016 wt.% Mn, and the balance is Mg) as the anode material, 0.1 M [Ch][GA], [Ch][SAL], [Ch][HQSA] (3.5 wt.% NaCl as solvent) as the electrolyte, and air cathode. The battery discharge performance was tested in the magnesium-air battery assembly kit using a Blue Electric Battery Test System (CT3001A) at current densities of 1, 2.5, and 5 mA cm −2 The discharge times were 24 h, 10 h, and 10 h, respectively. The Hp-Mg anode used for battery testing was encapsulated in silicone rubber, and the area exposed to the test solution was 1.0 cm 2 Before all experiments, the anode surface was treated as follows: mechanical grinding with sandpaper (metallographic sandpaper: 180-600-1500-3000), then cleaned with anhydrous ethanol, and dried at room temperature. The air cathode used was the air cathode M20 purchased from Changzhou Utech (composed of a gas diffusion layer, a current collecting layer and a catalytic layer, the catalytic layer including a manganese dioxide catalyst).
[0052] After the battery discharge test, 200 g L -1 The chromic acid solution is used to remove the reaction products on the anode surface. The specific energy of the magnesium-air battery is calculated by the following formula:
[0053]
[0054] Formula (1), in U (V) is the discharge voltage, W total (kg) is the weight loss of the anode after the full battery test, I (A) is the applied current, t(h) is the discharge time.
[0055] In Application Example 1, the discharge test results of the magnesium-air battery assembled with Hp-Mg anode in the choline-containing ionic liquid electrolyte are shown as follows (see Figure 1 and Table 1).
[0056] Table 1: Average discharge potential and specific energy values of magnesium-air batteries assembled with Hp-Mg anode in choline-containing ionic liquid electrolyte.
[0057]
[0058] Table 1 and Figure 1 It is shown that at current densities of 1 and 2.5 mA cm -2 Under the condition of 5 mA cm-2, the cell voltage of Hp-Mg in 0.1 M [Ch][GA] electrolyte is higher than that in blank electrolyte in the early stage of discharge, but the cell voltage decreases with the increase of discharge time until it is equivalent to the voltage value of blank electrolyte. -2 When the discharge reaction is intense, a large amount of Mg 2 + , resulting in [Ch][GA] complexing Mg 2+ The ability to generate Mg is lower than that of discharge 2+ Therefore, Mg(OH)2 and MgO are generated and deposited on the surface of the magnesium anode, and the battery voltage is reduced, even lower than that of the blank group. In addition, at these three current densities, the specific energy of the Hp-Mg-based magnesium-air battery in the electrolyte containing [Ch][GA] is significantly improved compared with the blank group, indicating that the addition of [Ch][GA] can improve the discharge performance of the magnesium-air battery.
[0059] At low current densities (1 and 2.5 mA cm -2 ), the cell voltage of Hp-Mg in 0.1 M [Ch][SAL] electrolyte was significantly higher than that in blank electrolyte, and the increase became smaller with the increase of current density; at a current density of 5 mA cm -2 Due to the intense discharge and the generation of a large amount of discharge products, the battery voltage of the test group is slightly lower than that of the blank group. -2 Although the addition of [Ch][SAL] to the electrolyte did not significantly increase the cell voltage of the Hp-Mg anode, the specific energy increased. The specific energy of the Hp-Mg-based magnesium-air battery in the electrolyte containing [Ch][SAL] was significantly improved compared with the blank group, and at 2.5 mA cm -2 , the specific energy reaches a maximum value of 2180.18 ± 178.32 Wh Kg -1 .
[0060] At three current densities, the cell voltage of Hp-Mg in 0.1 M [Ch][HQSA] electrolyte is significantly higher than that in blank electrolyte. -2 When the current density is 5 mA cm, the battery voltage in the [Ch][HQSA] electrolyte is the highest. In addition, at these three current densities, the specific energy of the Hp-Mg-based magnesium-air battery in the [Ch][HQSA] electrolyte is significantly improved compared with the blank group. -2 The specific energy of Hp-Mg-based magnesium-air battery in [Ch][HQSA]-containing electrolyte is as high as 1568.61 ± 23.59 Wh Kg -1 .
[0061] Therefore, adding the choline ionic liquids ([Ch][GA], [Ch][SAL] and [Ch][HQSA]) synthesized in the present invention into the electrolyte can effectively improve the discharge performance of the Hp-Mg magnesium anode-based magnesium-air battery.
[0062] Application Example 2
[0063] Taking choline salicylate ionic liquid [Ch][SAL] as an example, the effects of the ionic liquid on the discharge performance of magnesium-air batteries with AM50, AZ31 and ZK61 as anodes in 3.5 wt.% NaCl electrolyte were studied.
[0064] Taking magnesium alloy AM50 (the composition of AM50: 4.70 wt.% Al, 0.13 wt.% Zn, 0.03 wt.% Si, 0.002 wt.% Fe, 0.004 wt.% Cu, 0.001 wt.% Ni, 0.32 wt.% Mn, the balance is Mg), AZ31 (the composition of AZ31: 2.96 wt.% Al, 0.52 wt.% Zn, 0.16 wt.% Si, 0.003 wt.% Fe, 0.006 wt.% Cu, 0.001 wt.% Ni, 0.31 wt.% Mn, the balance is Mg), ZK61 (the composition of ZK61: 0.01 wt.% Al, 5.43 wt.% Zn, 0.01 wt.% Si, 0.008 wt.% Fe, 0.007 wt.% Cu, 0.004 wt.% Ni, 0.65 wt.% Zr, the balance is Mg) as the anode, 0.1 M [Ch][SAL] (3.5 wt.% NaCl as the solvent) as the electrolyte, and an air cathode to assemble a magnesium-air battery. The battery test method, anode treatment method, and specific energy calculation are the same as in Application Example 1.
[0065] Application Example 2 The discharge test results of magnesium-air batteries assembled with three different types of anodes in an electrolyte containing 0.1 M [Ch][SAL] are shown in Figure 2 and Table 2.
[0066] Table 2: Average discharge potential and specific energy values of magnesium-air batteries assembled with three types of anodes in an electrolyte containing 0.1 M [Ch][SAL].
[0067]
[0068] From Table 2 and Figure 2 It can be seen that at 1 mA cm -2 At the current density of 2.5 mA cm, the cell voltage of AM50 and AZ31 in [Ch][SAL] electrolyte is higher than that in blank electrolyte; -2 At the current density, the battery voltage of the test group was comparable to that of the blank group; however, at 5 mA cm -2 In the case of ZK61 anode, adding [Ch][SAL] will have an adverse effect on the cell voltage.
[0069] At 1, 2.5 and 5 mA cm -2 At a current density of , the specific energy of the magnesium-air batteries based on AM50 and AZ31 in the electrolyte of [Ch][SAL] is significantly improved compared with the blank group. In contrast, the increase in the specific energy of the magnesium-air battery based on the ZK61 anode decreases with the increase in the applied current density, but compared with the blank group, the specific energy after adding [Ch][SAL] is significantly improved. Therefore, adding [Ch][SAL] to the electrolyte can effectively improve the discharge performance of these three magnesium anode-based magnesium-air batteries.
[0070] In summary, the choline ionic liquid of the present invention, as an electrolyte additive, can greatly improve the discharge voltage and specific energy of the magnesium-air battery, greatly improve the discharge performance of the magnesium-air battery with Hp-Mg, AM50, AZ31 and ZK61 as the anode, and has great promotion and application value.
Claims
1. A choline ionic liquid, characterized in that: The structural formula is as follows: , The choline ionic liquid is used as an electrolyte additive for magnesium-air batteries.
2. The method for synthesizing the choline ionic liquid according to claim 1, characterized in that: The steps include: The choline hydroxide is mixed with an acid compound and distilled water, and then stirred at room temperature for 12-24 hours. After the reaction is completed, the mixture is subjected to rotary evaporation and drying to obtain the product; The acid compound is 8-hydroxyquinoline-5-sulfonic acid; The molar ratio of the choline hydroxide to the acid compound is 1:
1.
3. Use of the choline ionic liquid according to claim 1 as an electrolyte additive for magnesium-air batteries.
4. A magnesium-air battery, characterized in that: The invention comprises an anode material, an air cathode and an electrolyte containing the choline ionic liquid as claimed in claim 1 as an additive.
5. The magnesium-air battery according to claim 4, characterized in that: The electrolyte was 3.5 wt.% NaCl.
6. The magnesium-air battery according to claim 4, characterized in that: The anode material is one or more of Hp-Mg, AM50, AZ31 and ZK61 alloys.
Citation Information
Patent Citations
Ionic liquid composed of bio-relating compound
JP2008162899A
Electrolytes and Metal Hydride Batteries
US20160141724A1
Cited By
Magnesium battery rare earth chloride electrolyte and preparation method and use method thereof
CN120545570A
A magnesium battery rare earth chloride electrolyte and a preparation method and use method thereof
CN120545570B